FOREIGN EXPERIENCE OF PATRIOTIC EDUCATION - Afanasieva Yu. V. (Pressing Problems of Public Administration, 2017)
The paper analyses the grounds of patriotic education in some countries of the world (the USA, Great Britain, Germany, Lithuania, Latvia, Poland, Japan) according to the degree of state participation in this process. It is determined that there is a direct link between patriotic education and the process of education in many countries. It is de ned that in the countries of Western Europe in the process of developing democratic lifestyle, patriotic education has transformed into formation of civicism, based on the rights and freedoms of a person and citizen.